Ectopic overexpression of CD133 in HNSCC makes it resistant to commonly used chemotherapeutics. Issue 4 (April 2017) - Lee, Junyoung; Park, Mineon; Ko, Youngjong; Kim, Bora; Kim, Okjoon; Hyun, Hoon; Kim, DongHwi; Sohn, HongMoon; Moon, Young Lae; Lim, Wonbong
Head and neck squamous cell carcinoma (HNSCC) is one of the most common cancers in the world. Resistance to cytotoxic chemotherapy is a major cause of mortality in patients with HNSCC. A small subset of cancer cells called cancer stem cells (CSCs) may be key contributors to drug resistance and tumor recurrence in HNSCC. The aim of this study was to determine whether CD133, which maintains properties of CSCs, promotes chemoresistance by arresting cell cycle transition and reducing apoptosis in HNSCC cells. CD133 overexpression was examined in KB cells, and colony forming and aldehyde dehydrogenase activity assays were performed. To investigate the role of CD133 in chemoresistance, cell death was analyzed using 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT), Diff-Quick, flow cytometry, and western blot of apoptosis-related protein expression in fluorouracil (5-FU)- or cisplatin-treated cells. In addition, microarray and related protein expression assessments were performed to investigate the mechanism of chemoresistance against 5-FU and cisplatin in KB cells. Moreover, chemoresistance against 5-FU or cisplatin in a KB-inoculated mouse model was analyzed by hematoxylin and eosin staining, immunohistochemical study of CD133, and immunofluorescence of tumor tissue. In this study, we demonstrate that ectopic overexpression of CD133 significantly promotes properties of stemness in KB cell lines. Furthermore, CD133 promotes chemoresistance by arresting transition of the cell cycle and reducing apoptosis, which results in inhibition of tumor growth in 5-FU- or cisplatin-injected mouse tumor model. Taken together, our findings show that elevated levels of CD133 lead to HNSCC chemoresistance through increased stemness and cell cycle arrest.